Development and Use of a Real-Time Quantitative PCR Method for Detecting and Quantifying Equol-Producing Bacteria in Human Faecal Samples and Slurry Cultures - Vázquez, Lucía; Guadamuro, Lucía; Giganto, Froilán; Mayo, Baltasar; Flórez, Ana B. (Frontiers in Microbiology, 2017)
This work introduces a novel real-time quantitative PCR (qPCR) protocol for detecting and quantifying equol-producing bacteria. To this end, two sets of primers targeting the dihydrodaidzein reductase (ddr) and tetrahydrodaidzein reductase (tdr) genes, which are involved in the synthesis of equol, were designed. The primers showed high specificity and sensitivity when used to examine DNA from control bacteria such as Slackia isoflavoniconvertens, Slackia equolifaciens, Asaccharobacter celatus, Adlercreutzia equolifaciens and Enterorhabdus mucosicola. To demonstrate the validity and reliability of the protocol, it was used to detect and quantify equol-producing bacteria in human faecal samples and their derived slurry cultures. These samples were provided by 18 menopausal women under treatment of menopause symptoms with a soy isoflavone concentrate, among whom three were known to be equol-producers given the prior detection of the molecule in their urine. The tdr gene was detected in the faeces of all these equol-producing women at about 4-5 log10 copies per gram of faeces. In contrast, the ddr gene was only amplified in the faecal samples of two of these three women, suggesting the presence in the non-amplified sample of reductase genes unrelated to those known to be involved in equol formation and used for primer design in this study. When tdr and ddr were present in the same sample, similar copy numbers of the two genes were recorded. However, no significant increase in the copy number of equol-related genes along the treatment was observed. Surprisingly, positive amplification for both tdr and ddr genes was obtained in faecal samples and derived slurry cultures from two non-equol producing women, suggesting the genes could be non-functional or the daidzein metabolized to other compounds in samples from these two women. This novel qPCR tool provides a technique for monitoring gut microbes that produce equol in humans. Monitoring equol-producing bacteria in the human gut could provide a means of evaluating strategies aimed at increasing the endogenous formation of this bioactive compound.